2005
DOI: 10.1103/physrevlett.94.030402
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Quantized Displacement in Macroscopic Nanomechanical Oscillators

Abstract: We report the observation of discrete displacement of nanomechanical oscillators with gigahertz-range resonance frequencies at millikelvin temperatures. The oscillators are nanomachined single-crystal structures of silicon, designed to provide two distinct sets of coupled elements with very low and very high frequencies. With this novel design, femtometer-level displacement of the frequency-determining element is amplified into collective motion of the entire micron-sized structure. The observed discrete respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 34 publications
(36 reference statements)
1
83
0
Order By: Relevance
“…minute cantilevers, this would involve placing an object of many millions of atoms in a superposition state. However anti-intuitive this may appear, work has been recently reported that suggests this may indeed be possible 16,17 . Even if possible, such a device would not be at all easy to use, having to be operated at cryogenic temperatures to avoid decoherence due to thermal effects.…”
Section: Qubit Entanglement In An Optical Wavefront Processormentioning
confidence: 94%
“…minute cantilevers, this would involve placing an object of many millions of atoms in a superposition state. However anti-intuitive this may appear, work has been recently reported that suggests this may indeed be possible 16,17 . Even if possible, such a device would not be at all easy to use, having to be operated at cryogenic temperatures to avoid decoherence due to thermal effects.…”
Section: Qubit Entanglement In An Optical Wavefront Processormentioning
confidence: 94%
“…With respect to the (promising) applications and advantages of nanomechanical resonator, it still faces many serious technical challenges and difficulties, such as the fluctuation due to thermomechanical noise [10,20,21]; low Q factor with decreasing size [10,17,18,21,22], increasing magnetic field [21], increasing ambient pressure [4,21] and dynamic nonlinear response [3][4][5][6][7][8]10,11,21,23,24]. Recent findings on the initial conditions-dependent antiresonance response of weakly nonlinear nanomechanical resonator [24] and strongly nonlinear response of doubly clamped nanomechanical resonator [10] demonstrate some application limitations of nanomechanical resonators because of nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of electronic transistor and magnetic storage technologies in 1960s, which were much superior to the mechanism of mechanical moving element in both manipulation speed and data density, resulted in the abandonment of Babbage's idea of mechanical computer [19]. Recent breakthrough in the fabrication of NEMS resonator with the fundamental characteristic frequency of 1 GHz and higher [9,11] intrigues further research interest in this area because such breakthrough could eventually lead to the realization of high performance mechanical computer which can compete with current electronic computer. Mechanical resonator with GHz characteristic frequency which moves on time scale of a nanosecond or less makes such competition possible [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations